Artificial Intelligence in Quality Control Systems: A Cross-Industry Analysis of Applications, Benefits, and Implementation Frameworks - Divyansh Jain, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article presents a comprehensive analysis of artificial intelligence applications in quality control across manufacturing, service, and infrastructure maintenance sectors. The article examines how AI-driven systems are transforming traditional quality control processes through automated defect detection, real-time monitoring, and adaptive testing methodologies. Through systematic review of industry implementations and case studies, we investigate the impact of machine learning algorithms, computer vision systems, and deep learning applications on quality assurance processes. The findings demonstrate significant improvements in inspection accuracy, reduction in manual inspection requirements, and enhanced detection of subtle defects across various industrial applications. The article reveals that AI-driven quality control systems offer substantial benefits in terms of operational efficiency, cost reduction, and quality consistency, while also identifying key implementation challenges such as initial infrastructure requirements, data quality concerns, and workforce adaptation needs. Additionally, the article provides insights into emerging trends and future opportunities for AI integration in quality control systems, contributing to the broader understanding of Industry 4.0 implementation strategies. This work serves as a foundational reference for organizations considering AI implementation in their quality control processes and provides a framework for evaluating the potential benefits and challenges across different industrial contexts.
Keywords: Artificial Intelligence Quality Control; Machine Learning Inspection Systems; Industrial Process Automation; Smart Manufacturing Analytics; Quality Management Digitalization